الضرائب البيئية كأداة لتوجيه السلوك البيئي في الجزائر - حنكه, يوسف; حميداتو, صالح (جامعة الوادي - University of Eloued, 2023)
تهدف هذه الدراسة إلى إبراز الضرائب البيئية المكونة للجباية البيئية في الجزائر وتحليل تطور إيراداتها بإعتبارها من أهم الآليات الاقتصادية الناجعة لحماية البيئة من التلوث ، ومن أجل تحقيق أهداف هذه الدراسة تم إتباع المنهج التحليلي الوصفي، وتم التوصل من خلال ذلك إلى أن الضرائب البيئية التي تم فرضها هدفها تحسين سلوك الملوثين بحيث تم تأسيسها على أساس مبدأ "الملوث يدفع"، و بالتالي تعتبر وسيلة من وسائل مواجهة التلوث البيئي والحد منه بأسلوب إقتصادي هذا من جهة، ومن جهة أخرى تشكل إيراداتها موردا ماليا لتغطية النفقات الموجهة للحد من آثار التلوث وحماية البيئة. This study aims to highlight the environmental taxes that constitute environmental taxation in Algeria and analyze the evolution of its revenues as one of the most effective economic mechanisms for protecting the environment from pollution. In order to achieve the objectives of this study, the descriptive analytical approach was followed, and through this it was concluded that the environmental taxes that were imposed aim at improving the behavior of polluters, as they were established on the basis of the principle of "polluter pays". Therefore, the environmental taxes are considered a means of confronting and reducing environmental pollution in an economic way. In addition, the environmental taxes revenues constitute a financial resource to cover the expenditures directed at reducing the effects of pollution and protecting the environment
Environmental taxes as a tool to guide environmental behavior in Algeria
مقال
Keywords: التلوث البيئي؛ الضرائب البيئية؛ النظام الجبائي؛ البيئة.: Environmental pollution; Environment taxes; Tax system; Environment.